Gender Differences in Risk Assessment Among Youth Adjudicated to Juvenile Correctional Facilities - Ho, Taiping (Women & criminal justice, 2021)
The Indiana Department of Corrections (IDOC) uses the IYAS-RES, a risk assessment tool comprised of the following domains: juvenile justice history; family and living arrangements; peers and social support network; education and employment; pro-social skills; substance abuse, mental health, and personality; and values, beliefs, and attitudes. Using a sample of 3,144 juveniles adjudicated to Indiana juvenile correctional facilities, this study examines gender differences in the risk assessment instrument. Results of the study indicated that there were gender differences in all but one of the risk assessment domains (values, beliefs, and attitudes). This study also found that females had higher total risk assessment scores than males, especially for domains that more directly capture female-specific pathways to crime. Results from OLS regression, however, found that males were assessed at higher overall risk levels than females, net of controls. These findings suggest a need to utilize more gender responsive assessment instrument.